Анксиозност поврзана со смртта кај млади возрасни: полови разлики и емоционални корелати - Наумова, Катерина; Поповски, Михајло (Faculty of Philosophy, Skopje, 2015)
Death anxiety is defined as an emotional response to awareness of death, including fear of personal mortality, which is not caused by an imminent threat to life. Numerous empirical findings suggest that the period of early adulthood is marked by a higtened fear or anxiety associated with death and dying, and that this type of anxiety is usually more prominent in females. According to the Terror Management Theory, adult attachment represents a distant defense from mortality salience and the transience of life. The study presented in this paper was conducted in order to examine sex differences in death anxiety in young adults, to analyze the relationship between death anxiety and certain emotional correlates (aging anxiety, empathy and adult attachment),as well as to assess the contribution of each emotional correlate in the prediction of death anxiety. The participants in the study were 435 undergraduate students from two universities in Macedonia. The data was gathered with Templer/McMordie Death Anxiety Scale, Anxiety about Aging Scale, Interpersonal Reactivity Index and Adult Attachment Scale. The assessment of sex differences showed that females feel significantly more anxious and fearful than males when thinking about death. Nearly all tested correlates were significantly associated with anxiety as a response to awareness of death, but the highest correlation exists between death anxiety and aging anxiety, personal distress and emphatic concern as affective components of empathy, and anxious attachment. The first three correlates are significant predictors of death anxiety, that explain over a third in its variance. The findings are aligned with developmental aspects of death anxiety and terror management theory.
Death anxiety in young adults: sex differences and emotional correlates
Keywords: death anxiety, aging anxiety, empathy, adult attachment, terror management theory